Between devotional practice and propaganda: : miraculous images of the Virgin Mary in Marian pilgrimage churches in Slovenian Styria - Bratuša, Tina (CEM – Cultura, Espaço & Memória, 2022)
The purpose of this paper is to discuss different aspects of the miraculous depictions of the Virgin Mary in selected Marian pilgrimage churches in Styria, Slovenia. The paper focuses in particular on the devotional practices and propaganda context associated with such depictions of the Virgin Mary. Throughout history Styrians — Slovenian and Austrian alike — have been particularly strongly attached to the Virgin Mary as the patron of the Habsburg lands. Consequently, miraculous images of the Virgin Mary in various forms were widespread. The immense popularity of the Virgin Mary and the miraculousness attributed to her images encouraged the foundation of many pilgrim routes and churches. The importance of such images can be seen in ex-votos, miracle books, the depictions of miracles in church interiors as well as the numerous holy cards, not to mention the diverse devotional practices.